Development of occupational safety and health requirement management system (OSHREMS) software using adobe dreamweaver CS5 for building construction project - Abas, Nor Haslinda; Adman, Nurjeha; Deraman, Rafikullah (EDP Sciences, 2017)
The construction industry sector is considered as being risky with frequent and high accident rate. According to Social Security Organization (SOCSO), the construction accidents has arisen from time to time. Construction Industry Development Board (CIDB) has developed the Safety and Health Assessment System in Construction (SHASSIC) for evaluating the performance of a contractor in construction project by setting out the safety and health management and practices, however the requirement checklist provided is not comprehensive. Therefore, this study aims to develop a software system for facilitating OSH in building construction project, namely OSH requirements management system (OSHREMS), using Adobe Dreamweaver CS5 and Sublime Text as PHP editor. The results from a preliminary study which was conducted through interviews showed that, the respondents were only implementing the basic requirements that comply with legislations, with the absence of appropriate and specific guideline in ensuring occupational safety and health (OSH) at the workplace. The tool will be benefits for contractors and other parties to effectively manage the OSH requirements for their projects based on project details.